LADDER DRILL DALAM MENINGKATKAN KELINCAHAN ATLET BOLA VOLI - Maretno Maretno; Arisman Arisman (PRODI PJKR UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2020)
This study aims to determine the results of the ladder drill on the agility of the Volleyball Unisma Bekasi Student Activity Unit (UKM) participants. This study used an experimental method with agility test instruments. The sample in this study was the participants of the UKM Bola voli Unisma Bekasi, amounting to 20 people with the sampling technique using purposive sampling. The results of this study indicate that there is an effect of ladder drill on agility, these results are evidenced by the results of the t-test, it is found that the results of t-count are greater than t table (6,214> 1,729), meaning that they have a significant effect on increasing agility.